Can Psychophysics Be Fun? Exploring the Feasibility of a Gamified Contrast Sensitivity Function Measure in Amblyopic Children Aged 4–9 Years - Elfadaly, Doaa; Abdelrazik, Sahar Torky; Thomas, Peter B. M.; Dekker, Tessa M.; Dahlmann-Noor, Annegret; Jones, Pete R. (Frontiers in Medicine, 2020)
Routine assessments of the Contrast Sensitivity Function [CSF] could be useful for the diagnosis and monitoring of amblyopia. However, current CSF measures are not clinically practical, as they are too slow, too boring, and too uncomfortable to sustain a young child’s interest. Here we assess the feasibility of a more gamified approach to CSF testing, in which a maximum likelihood psychophysical algorithm (QUEST+) is combined with a largely unconstrained user interface (no fixation target, head restraints, or discrete trials). Twenty-five amblyopes (strabismic, anisometropic, or mixed) aged 4.0 to 9.2 years performed the gamified CSF assessment monocularly (once per eye). The test required the child to ‘pop’ (press) grating stimuli as they “bounced” around a tablet screen. Head tracking via the tablet’s front-facing camera was used to adjust for variations in viewing distance post hoc. CSFs were fitted for each eye, and Area Under the CSF (AUCSF) computed as a summary measure of sensitivity. The results showed that AUCSF measurements were able to separate moderately and severely amblyopic eyes from fellow eyes (case-control effect), and to distinguish individuals with varying degrees of vision loss (dose effect). Even the youngest children exhibited no difficulties completing the test or comprehending what to do, and most children appeared to find the test genuinely enjoyable. Informal feedback from a focus group of older children was also positive, although potential shortcomings with the present design were identified. This feasibility study indicates that gamified, child-friendly vision assessments show promise as a future means of pediatric clinical assessment. Such measures could be particularly valuable for assessing children outside of conventional eye-care facilities (e.g., home-monitoring, school screening).